2023
DOI: 10.1001/jamanetworkopen.2023.23741
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Digital Health Technologies for Opioid Use Disorder Treatment by US Health Care Organizations

Abstract: ImportanceDigital health technologies may expand organizational capacity to treat opioid use disorder (OUD). However, it remains unclear whether these technologies serve as substitutes for or complements to traditional substance use disorder (SUD) treatment resources in health care organizations.ObjectiveTo characterize the use of patient-facing digital health technologies for OUD by US organizations with accountable care organization (ACO) contracts.Design, Setting, and ParticipantsThis cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…A recent study found that 34% of accountable care organizations servicing persons with OUD used some type of technology, virtual peer support, or digital recovery support services. 72 While many of these programs are not intended to directly expand buprenorphine treatment, they could increase provider confidence with prescribing by improving access to complementary care strategies. Examples include the use of virtual reality-based interventions to support remote counseling or cue-exposure and extinction paradigms 73 74 or chat-bots for counseling or social connection.…”
Section: Examples and Opportunities For Innovationmentioning
confidence: 99%
“…A recent study found that 34% of accountable care organizations servicing persons with OUD used some type of technology, virtual peer support, or digital recovery support services. 72 While many of these programs are not intended to directly expand buprenorphine treatment, they could increase provider confidence with prescribing by improving access to complementary care strategies. Examples include the use of virtual reality-based interventions to support remote counseling or cue-exposure and extinction paradigms 73 74 or chat-bots for counseling or social connection.…”
Section: Examples and Opportunities For Innovationmentioning
confidence: 99%
“…This study focused on a patient population with a previously diagnosed mood disorder for several reasons. There are parallel studies by several members of this research group, and the co-authors on this study have ongoing research and recent published studies involving the MindLAMP app for digital phenotyping investigations that focus on other patient populations, namely those of psychotic disorders [10] and substance use disorders [11]. The existing literature on digital phenotyping of mood disorders is limited and warrants its own dedicated investigation.…”
Section: Study Populationmentioning
confidence: 99%
“…The average number of digital health tools used by a physician growing from 2.2 to 3.8 over that same time period [ 2 ]. In a recent cross-sectional study of United States (US) accountable care organizations by Miller–Rosales et al, approximately one-third of the organizations surveyed integrated at least one digital health technology at the system level to support treatment of opioid use disorder (OUD) [ 3 ]. Overall, digital health technologies are being used to improve access, increase quality, personalize medicine, and reduce both costs and inefficiencies [ 1 ].…”
Section: Introductionmentioning
confidence: 99%